The Impact of Supply Chain Management on Mar-keting Frontiers in Competitive Business Building - Mikhail Shchepakin; Eva Frisovna; Juliana Bzhennikova; Olga Tolmacheva; Yuriy Bazhenov (International Journal of Supply Chain Management, 2018)
This article connects the positive market transformations with the role of business entities and supply chain management in marketing stepped up against the innovation-driven transformations. There are grounds laid for the necessity of extending the interdisciplinary approach to managing enterprise communications through motivation when organizing the marketing communication space. Article outlines the most important functions of business in the context of unstable economy and various dissonances. It discloses the economic nature of supply chain management, marketing frontier and simulation marketing in rational marketing business building. Marketing competitiveness thresholds were analyzed by effect on the marketing value of finished products. As it was found, significant discrepancy between motivation and resources available to the business entity and consumers gives rise to asymmetric marketing activities. The relevance of this article is that it provides more insights upon the processes and phenomena that occur when building models for managing the marketing behavior of subjects on the principles of rationality, required marketing value and integrative communication multiplier effect. This article introduces a model for managing product competitiveness by boosting the marketing frontier and adapting the marketing behavior of subject and supply chain management to unstable economy.